Building team spirit : activities for inspiring and energizing teams - Heermann, Barry (Mc Graw Hill New YorkUS, 1997)
Targets team leaders, organizational development facilitators, human resource development facilitators, trainers and consultants who need practical approaches to nurturing high-performance teams. Presents the 6 phases of team development as: initiating, visioning, claiming, celebrating, letting go, and service; and advances storytelling as a powerful tool for achieving team spirit. Provides 49 team activities complete with learning goals, preparation tasks, learning activities, methodology, learning and teaching materials, and expected outcomes. Includes learning goals such as: realizing the importance of celebrating based on the team's record of achievement; and, identifying an area of team dissonsance and developing action steps to respond to the dissonance.